Optimising the Design of Fe0-Based Filtration Systems for Water Treatment: The Suitability of Porous Iron Composites - Rahman, Mohammad Azizur; Karmakar, Shyamal; Salama, Heba; Gactha-Bandjun, Nadège; K., Brice Donald Btatkeu; Noubactep, Chicgoua (Journal of Applied Solution Chemistry and Modeling, 2013)
This study assessed the functionality of metallic iron (Fe0) filtration systems using porous iron composite (PIC) as an alternative to granular Fe0/aggregate mixtures. The usage of PIC for water treatment has many challenges which are related to the well-drained nature of highly porous filters and the corresponding increase in hydraulic conductivity (shorter contact time). In this article, the extent of (i) iron exhaustion and (ii) porosity loss in four filtration systems are critically discussed. The considered filtration systems are: (i) Fe0 alone, (ii) PIC alone, (iii) Fe0/sand and (iv) Fe0/pumice. In all four systems, mono-sized granular spherical particles are assumed. Sand and Fe0 are compact (f = 0 %) whereas PIC and pumice are porous (e.g. f = 40 %). Results demonstrated that under anoxic conditions (Fe3O4 as major corrosion products) Fe0 depletion is possible in all systems except Fe0 alone. Under oxic conditions (e.g. formation of Fe(OH)3), the PIC system exhibited the highest level of Fe0 depletion (58 %). The increasing order of sustainability was: Fe0 < Fe0/sand < Fe0/PM < PIC. These results suggested that manufacturing PIC with defined porosity and intrinsic reactivity is the key for more efficient usage of Fe0 for environmental remediation and water treatment.